Adipose Tissue as a Site of Toxin Accumulation. Issue 4 (12th September 2017) - Jackson, Erin; Shoemaker, Robin; Larian, Nika; Cassis, Lisa
ABSTRACT: We examine the role of adipose tissue, typically considered an energy storage site, as a potential site of toxicant accumulation. Although the production of most persistent organic pollutants (POPs) was banned years ago, these toxicants persist in the environment due to their resistance to biodegradation and widespread distribution in various environmental forms (e.g., vapor, sediment, and water). As a result, human exposure to these toxicants is inevitable. Largely due to their lipophilicity, POPs bioaccumulate in adipose tissue, resulting in greater body burdens of these environmental toxicants with obesity. POPs of major concern include polychlorinated biphenyls (PCBs), polychlorinated dibenzo‐p‐dioxins and furans (PCDDs/PCDFs), and polybrominated biphenyls and diphenyl ethers (PBBs/PBDEs), among other organic compounds. In this review, we (i) highlight the physical characteristics of toxicants that enable them to partition into and remain stored in adipose tissue, (ii) discuss the specific mechanisms of action by which these toxicants act to influence adipocyte function, and (iii) review associations between POP exposures and the development of obesity and diabetes. An area of controversy relates to the relative potential beneficial versus hazardous health effects of toxicant sequestration in adipose tissue. © 2017 American Physiological Society. Compr Physiol 7:1085‐1135, 2017.